The Association Between Mild Intraoperative Hypotension and Stroke in General Surgery Patients. (October 2016) - Hsieh, Jason K.; Dalton, Jarrod E.; Yang, Dongsheng; Farag, Ehab S.; Sessler, Daniel I.; Kurz, Andrea M.
Abstract : BACKGROUND: Intraoperative hypotension may contribute to perioperative strokes. We therefore tested the hypothesis that intraoperative hypotension is associated with perioperative stroke. METHODS: After institutional review board approval for this case-control study, we identified patients who had nonneurological, noncardiac, and noncarotid surgery under general anesthesia at the Cleveland Clinic between 2005 and 2011 and experienced a postoperative stroke. Control patients not experiencing postoperative stroke were matched in a 4-to-1 ratio using propensity scores and restriction to the same procedure type as stroke patients. The association between intraoperative hypotension, measured as time-integrated area under a mean arterial pressure (MAP) of 70 mm Hg, and postoperative stroke was assessed using zero-inflated negative binomial regression. RESULTS: Among 106 337 patients meeting inclusion criteria, we identified 120 who had confirmed postoperative stroke events based on manual chart review. Four-to-one propensity matching yielded a final matched sample of 104 stroke cases and 398 controls. There was no association between stroke and intraoperative hypotension. Stroke patients were not more likely than controls to have been hypotensive (odds ratio, 0.49 [0.18–1.38]), and among patients with intraoperative hypotension, stroke patients did not experience a greater degree of hypotension than controls (ratio of geometric means, 1.07 [0.76–1.53]). CONCLUSIONS: In our propensity score–matched case-control study, we did not find an association between intraoperative hypotension, defined as MAP < 70 mm Hg, and postoperative stroke. Abstract : Supplemental Digital Content is available in the text.